The Media Characteristics and Subject Boundaries of Metaverse Art. - Xiong, Yiran (Critical Arts: A South-North Journal of Cultural & Media Studies)
Digitization is the primary form of Metaverse art, making the Metaverse digitally re-enable the unfolding of art. First, as a digital art form, non-fungible token (NFT) art acts as a media technology object for digital subjects to seek an identity. It opens the potential to reflect on image ontology and image copies. Second, the development of Metaverse art is closely related to its media characteristics. The exploration of the attributes of Metaverse media can be divided into two approaches. One approach is to examine the characteristics of Metaverse media from the perspective of media archaeology and its association with cinema and games. The second approach lies in elucidating the temporal mechanism of modernity rooted in Metaverse media and rethinking the prominence and intervention of an "algorithmic timeline" in real time. Finally, the mediating properties of digital image ontology and the Metaverse's temporal and spatiotemporal folding correspond to the two main characteristics of immersion and interactivity in a virtual space, which not only reflects the generation of an "external subject" but also triggers a crisis in the identification of the subject with the mirror image.